2002
DOI: 10.2337/diabetes.51.10.2951
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Visceral Fat Prevents Insulin Resistance and Glucose Intolerance of Aging

Abstract: Age-dependent changes in insulin action and body fat distribution are risk factors for the development of type 2 diabetes. To examine whether the accumulation of visceral fat (VF) could play a direct role in the pathophysiology of insulin resistance and type 2 diabetes, we monitored insulin action, glucose tolerance, and the expression of adipo-derived peptides after surgical removal of VF in aging (20-month-old) F344/Brown Norway (FBN) and in Zucker Diabetic Fatty (ZDF) rats. As expected, peripheral and hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
398
2
11

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 515 publications
(451 citation statements)
references
References 46 publications
(43 reference statements)
28
398
2
11
Order By: Relevance
“…Aged F344/BN rats are associated with insulin resistance and glucose intolerance, as shown in several previous reports [15,18,44]. In the present study, we also observed impaired glucose tolerance, as indicated by the elevated blood glucose levels after glucose loading in the aged obese F344/BN rats.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Aged F344/BN rats are associated with insulin resistance and glucose intolerance, as shown in several previous reports [15,18,44]. In the present study, we also observed impaired glucose tolerance, as indicated by the elevated blood glucose levels after glucose loading in the aged obese F344/BN rats.…”
Section: Discussionsupporting
confidence: 91%
“…This increase in body weight with age is a major risk factor for insulin resistance, diabetes and ath-erosclerotic cardiovascular disease [15]. Aged mice and rats are associated with reduced hypothalamic Pomc expression [12], and the induction of Pomc by exogenous leptin is impaired with ageing [16].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the non-availability of fat substrate, muscle insulin responsiveness was very high but could be reversed by fat implantation. Similarly, the surgical excision of visceral fat in ageing Zucker diabetic and FBN insulin-resistant rats markedly improved the peripheral and hepatic insulin action [98]. In high fat fed rats, treatment with another TZD, BRL49653, reduced systemic NEFA and pronouncedly improved insulin action and glucoregulation [99].…”
Section: Fat Metabolism Targeted Antidiabetic Modalitiesmentioning
confidence: 98%
“…The mesenteric fat was left intact because of the high morbidity associated with its removal. The amount of VF removed was ϳ10 -20% of total fat mass (13). For sham operations, the abdominal cavity was incised, and the VF was mobilized from its surrounding tissues but not removed.…”
Section: Methodsmentioning
confidence: 99%
“…Central obesity is considered to be an essential component of the metabolic syndrome (1), and increased visceral fat is associated with decreases in peripheral and hepatic insulin sensitivity (5,9,14). Surgical extraction of visceral fat has been shown to reverse insulin resistance in young obese and old male rodents (13) and to delay the onset of diabetes in Zucker rats, a model of progressive obesity and diabetes (13). During pregnancy, maternal body fat increases on average Ͼ3 kg (19), with indirect evidence to suggest that visceral fat increases in particular (21).…”
mentioning
confidence: 99%